PENERAPAN DATA MINING UNTUK MEMPREDIKSI KELAYAKAN KREDIT NASABAH PADA PT. BPR INDOBARU FINANSIA MENGGUNAKAN ALGORITMA C4.5 - Tuhumena, Melva marsyah adella; Arnomo, Sasa Ani (LPPM Universitas Putera Batam, 2022)
The purpose of this study is to find out how to use data mining to assist banks in deciding which customers are eligible for credit in order to reduce credit congestion with the C4.5 algorithm method. which may be applied to BPR Indobaru Finansia. The indicators in this study are employment, character, loan ceiling, income, guarantees and decisions that will be processed using the weka application. Predicting creditworthiness using data from prospective customers at PT BPR Indobaru Finansia as an explanation or guide when making a decision tree.